DETERMINASI PERTUMBUHAN EKONOMI PROVINSI JAWA BARAT - Farah Diffa Hanum (2021)
Economic growth is an important indicator in the success of economic development for a country. The indicators used to influence economic growth include the human development index, labor, and government expenditure. The purpose of the research is to analyze the variables that affect the economic growth of West Java Province from period 2017 to 2020. The analysis technique is Panel Data regression using the Fixed Effect Model (FEM), with the help of Microsoft Excel 2016 and the data is processed using Eviews 12 with a significance of 5%. The results showed that Human Development Index and Government Expenditure affect Economic Growth a significant positive, while Labor doesn't affect Economic Growth.